PENGARUH LITERASI KEUANGAN SYARIAH DAN INKLUSI KEUANGAN SYARIAH TERHADAP KINERJA UMKM (Studi Kasus pada UMKM Area relokasi Alun – alun Kejaksaan Cirebon) - Dian Wulandari (UIN Siber Syekh Nurjati Cirebon, 2023)
MSME as a business is run by many middle to lower economic class people, so that MSME actors can make various efforts to help the economy. This study uses a descriptive quantitative approach. The results of this study are: Partially, the Islamic financial literacy variable partially has a positive, and significant influence on MSME performance variables with tcount (5.498) > ttable (0.842). And, the Islamic financial inclusion variable partially has a positive, and significant influence on MSME performance variables with a tcount (5.161) > ttable (0.029). Furthermore, simultaneously the Islamic financial literacy variables and Islamic financial inclusion simultaneously influence the MSME performance variables significantly with Fcount (331.524) > Ftable (2.93).Â Keywords: Islamic Financial Literacy; Islamic Financial Inclusion; Performance, MSMEs